DISTRIBUTION OF EARTH PRESSURE ON RETAINING WALL WITH "NARROW" FLAT SURFACE AREAS LOADING LOADING - , И. Я., А. М. (Municipal economy of cities. Series: «Economy science», 2013)
We consider the behavior of the active earth pressure in the presence of retaining walls for filling the small width of the strip loads.